1982
DOI: 10.1128/jcm.16.2.387-390.1982
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of human rotaviruses in primary cultures of monkey kidney cells

Abstract: We succeeded in isolating human rotaviruses from the feces of gastroenteritis patients by using roller cultures of primary cynomolgus monkey kidney cells with trypsin in the maintenance medium but without concentration and trypsin treatment of the inocula at each passage level. These cells were found to be more sensitive than MA-104 cells (derived from fetal rhesus monkey kidney) for the propagation of human rotaviruses. Polyacrylamide gel electrophoresis of the genome RNA revealed that there were small differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…The only exception of which we are aware and in which a significant number of isolates were analyzed was conducted in the Mexico City area from 1984 to 1987 (52). In that study, 29,11,10, and 17% of the isolates belonged to serotypes 1 to 4, respectively. The others (33%) were again not typeable.…”
Section: IImentioning
confidence: 97%
See 1 more Smart Citation
“…The only exception of which we are aware and in which a significant number of isolates were analyzed was conducted in the Mexico City area from 1984 to 1987 (52). In that study, 29,11,10, and 17% of the isolates belonged to serotypes 1 to 4, respectively. The others (33%) were again not typeable.…”
Section: IImentioning
confidence: 97%
“…Previous results indicated that two passages in African green monkey kidney cells before inoculation of a continuous cell line greatly increased the probability of success in culture adapting human rotaviruses from stool specimens (69). Others have also reported more efficient cell culture adaptation of human rotaviruses if initial passage was in primary monkey kidney cells (1,29,74).…”
Section: IImentioning
confidence: 99%
“…About 40% of diarrhea cases in young children are due to rotavirus infections (10). Recently, human rotaviruses from countries with a temperate climate have been successfully cultivated in tissue cultures (5,9,14,15), which gives us a possibility of developing rotavirus vaccines with the tissue culture-adapted strains. However, cultivation and characterization of rotaviruses of the tropical areas, where rotavirus is medically more important than in the northern countries, has not been reported.…”
mentioning
confidence: 99%
“…The antigen-positive specimens were subjected to virus isolation in roller cultures of primary cynomolgus monkey kidney cells in maintenance medium containing trypsin as described previously (5). From 41 specimens, 23 viruses were isolated: 16 strains of rotaviruses, two strains of adenovirus type 7, one strain of poliovirus type 1 and two strains of poliovirus type 3, one strain each of echovirus type 8 and 16, and an unidentified enterovirus-like agent.…”
mentioning
confidence: 99%
See 1 more Smart Citation